Trial of labour versus elective caesarean delivery for estimated large for gestational age foetuses after prior caesarean delivery: a multicenter retrospective study - Matthieu Chamagne; Maêva Bôle Richard; Alexandre Vallee; Jellila Tahiri; Bruno Renevier; Sandra Dahlhoff; Diane Garcia; Alexandre Vivanti; Jean Marc Ayoubi (BMC, 2023)
Abstract Background Lower rates of successful trial of labor after cesarean (TOLAC) in association with fetal macrosomia were previously reported. This study aimed to compare TOLAC to elective caesarean delivery (CD) in women with estimated fetal weight large for gestational age (eLGA) and a prior CD. Primary outcome was to analyse the mode of delivery in case of TOLAC. Secondary outcome was to compare maternal and foetal morbidity. Methods We conducted a retrospective, descriptive, multicentric, cohort study in five maternity units between January and December 2020. Inclusion criteria were: women with a single prior CD and eLGA or neonatal weight > 90th percentile with singleton pregnancy and gestational age ≥ 37 weeks. Main outcome measures: rate of vaginal delivery, maternal and fetal morbidity including: shoulder dystocia, neonatal hospitalization, fetal trauma, neonatal acidosis, uterine rupture, 3rd and 4th perineal tears, post-partum hemorrhage, and a need for blood transfusion. Results Four hundred forty women met inclusion criteria, including 235 (53.4%) eLGA. 170 (72.3%) had a TOLAC (study group) and 65 (27.7%) an elective CD (control). 117 (68.82%) TOLAC had a vaginal delivery. No significant differences were found between the two groups in the rates of: postpartum haemorrhage, transfusion, Apgar score, neonatal hospitalization, and foetal trauma. Cord lactate was higher in the case of TOLAC (3.2 vs 2.2, p < 0.001). Median fetal weight was 3815 g (3597-4085) vs. 3865 g (3659-4168): p = 0.068 in the study vs. controls group respectively. Conclusion TOLAC for eLGA fetuses is legitimate because there is no difference in maternal-fetal morbidity, and the CD rate is acceptable.